The assistant [videorecording (DVD)] - Green, Kitty (Filmmaker); Green, Kitty (Filmmaker); Garner, Julia, 1994-; Macfadyen, Matthew, 1974-; Leigh, Makenzie, 1990- (Universal Pictures Home Entertainment, 2020)
Follows a day in the life of an assistant to a powerful executive as she endures a variety of abuses.